Identities with Generalized Derivations and Automorphisms on Semiprime Rings - Ali, Asma; Khan, Shahoor; Hamdin, Khalid Ali (Journal of Advances in Applied & Computational Mathematics, 2015)
In this paper we prove some results which extend Theorem 4, Theorem 10 and Theorem 11 of Vukman [13] and proposition 2.3 of Thaheem and Samman [10].